2008
DOI: 10.1021/la802340g
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Efficient Dye-Sensitized Solar Cells by Introducing an Interfacial Layer of Long-Range Ordered Mesoporous TiO2 Thin Film

Abstract: Long-range ordered cubic mesoporous TiO 2 films with 300 nm thickness were fabricated on fluorine-doped tin oxide (FTO) substrate by evaporation-induced self-assembly (EISA) process using F127 as a structure-directing agent. The prepared mesoporous TiO 2 film (Meso-TiO 2) was applied as an interfacial layer between the nanocrystalline TiO 2 film (NC-TiO 2) and the FTO electrode in the dye-sensitized solar cell (DSSC). The introduction of Meso-TiO 2 increased J sc from 12.3 to 14.5 mA/cm (2), and V oc by 55 mV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 48 publications
3
63
0
1
Order By: Relevance
“…Currently various heat-resistant substrates such as Pyrex glass [16,17,45,66], fused silica [51], transparent conductive oxide (TCO) [67][68][69][70][71], quartz [46], stainless steel [72][73][74], Ti foil [50], and silicon [15,75,76] have been employed for film deposition. The nature of coating substrates, particularly the surface roughness, has found to exert an influence on the mesostructural regularity of the mesoporous TiO 2 films [77].…”
Section: Film Depositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently various heat-resistant substrates such as Pyrex glass [16,17,45,66], fused silica [51], transparent conductive oxide (TCO) [67][68][69][70][71], quartz [46], stainless steel [72][73][74], Ti foil [50], and silicon [15,75,76] have been employed for film deposition. The nature of coating substrates, particularly the surface roughness, has found to exert an influence on the mesostructural regularity of the mesoporous TiO 2 films [77].…”
Section: Film Depositionmentioning
confidence: 99%
“…Generally, the degree of long-range ordering is deteriorated with increase of the substrate roughness. Based on small-angle XRD, TEM and AFM characterizations, Lee's group [45,69,70] have revealed that the long-range ordering of the mesoporous structure may be deteriorated when the substrate is changed from Pyrex glass to FTO and then to ITO conducting glasses. That is, highly organized cubic mesoporous structure was obtained on the smooth Pyrex glass, whereas only worm-like mesoporous structure was formed on the rough ITO glass.…”
Section: Film Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is similar to the FTO-glass-based DSSC after introduction of a highly crystalline blocking layer at the interface of the FTO glass and TiO 2 electrode. [ 34 ] We have introduced a very simple, but highly effective, surface-treatment method for the use of Ti foil as a substrates for photoelectrode in DSSCs. When a Ti substrate was treated with an aqueous HNO 3 -HF solution, both the surface morphology and the crystalline structure of the thermally oxidized layer were varied.…”
Section: Transformation (Fft) Diffractogram (Figure 2 a And B)mentioning
confidence: 99%